Stress-state dependent cohesive model for fatigue crack growth (Fracture and Structural Integrity, 2016)
In the cohesive framework, a stress-state dependent cohesive model, combined with an irreversible damage parameter has been used in simulation of fatigue crack growth initiation and continued growth. The model is implemented as interface elements and plane strain simulations of crack initiation and growth under cyclic loading are performed. The stressstate of neighboring continuum elements is used in the traction-separation behavior of the cohesive elements. The model is shown to be able to reproduce the typical initiation life as well as fatigue crack growth curves. Further, the effect of the cohesive fatigue parameter on the initiation life and crack growth rates is established. KEYWORDS. Cohesive zone model; Fatigue; Triaxiality; Stress state.
Keywords: Cohesive zone model; Fatigue; Triaxiality; Stress state